Multi-century periods since fire in an intact woodland landscape favour bird species declining in an adjacent agricultural region. (February 2019) - Gosper, Carl R.; Fox, Elizabeth; Burbidge, Allan H.; Craig, Michael D.; Douglas, Tegan K.; Fitzsimons, James A.; McNee, Shapelle; Nicholls, A.O.; O'Connor, James; Prober, Suzanne M.; Watson, David M.; Watson, Simon J.; et al.
Abstract: Habitat modification by fire and habitat loss via anthropogenic vegetation clearance and fragmentation both impact animal populations. Yet, there has been limited investigation as to whether animals that decline under one of these types of habitat change also decline under the other, and how their cumulative impacts affect the status of species and communities. Using a ~400-year chronosequence in the world's largest extant temperate woodland in south-western Australia, we examine how time since fire affects bird community richness, reporting rates and composition, and whether taxa grouped on the basis of responses to vegetation clearance and fragmentation in an adjoining agricultural landscape are associated with either recently-burnt or long-unburnt woodlands. Consistent with substantial changes in vegetation composition and structure after fire in obligate-seeder eucalypt woodlands, woodland bird communities were strongly affected by fire. Species richness and total reporting rates increased with time since fire, and community composition changed across the entire multi-century span of the chronosequence. Woodland birds most negatively impacted by vegetation clearance and fragmentation were strongly associated with long-unburnt woodlands. In a regional south-western Australian context, where extensive vegetation clearance has substantially reduced the range and populations of many woodland bird species, the ability of remaining unfragmented woodlands to support populations of these species will be strongly contingent on appropriate fire management. Specifically, as stand-replacement fires have affected 25–30% of extant woodland over recent decades, management to limit the extent of fire in remaining long-unburnt woodlands would appear a priority for conservation of woodland bird diversity.